2013
DOI: 10.1097/iop.0b013e31826e4d75
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surgical Technique for the Treatment of Giant Fornix Syndrome

Abstract: The authors' novel surgical technique helps restore the abnormal anatomy found in patients with giant fornix syndrome and thus, helps resolve chronic relapsing conjunctivitis and surface disease associated with this often underdiagnosed condition. Further studies are needed to evaluate the risk of entropion and dry eye syndrome due to the modification of the posterior lamella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Nabavi et al 7 have also reported successful outcomes from GFS surgery in a series of 6 cases. Their procedure differs from ours in the following ways: 1) Nabavi et al reduced the depth of both upper and lower fornices in all cases.…”
Section: Gfs and Fornix Depthmentioning
confidence: 90%
See 1 more Smart Citation
“…Nabavi et al 7 have also reported successful outcomes from GFS surgery in a series of 6 cases. Their procedure differs from ours in the following ways: 1) Nabavi et al reduced the depth of both upper and lower fornices in all cases.…”
Section: Gfs and Fornix Depthmentioning
confidence: 90%
“…Forniceal depth was measured with a Bowmans probe marked with 1 mm graduations as described by Turner et al 6 The surgical procedure for forniceal shortening was similar to that described by Nabavi et al 7 and was as follows:…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Deep conjunctival fornices in affected patients can be a site for prolonged sequestration of bacteria causing recurrent infections. 15,16 Deep conjunctival fornices in affected patients can be a site for prolonged sequestration of bacteria causing recurrent infections.…”
Section: Entropion and Ectropionmentioning
confidence: 99%
“…15,16 Deep conjunctival fornices in affected patients can be a site for prolonged sequestration of bacteria causing recurrent infections. 15,16 Particularly, patients with unilateral symptoms in the absence of nasolacrimal duct obstruction should raise suspicion of GFS. 15,16 Particularly, patients with unilateral symptoms in the absence of nasolacrimal duct obstruction should raise suspicion of GFS.…”
Section: Entropion and Ectropionmentioning
confidence: 99%
See 1 more Smart Citation